Flower of capitalism : South Korean advertising at a crossroads - Fedorenko, Olga (Hawaiʻi studies on Korea., 2022)
An ethnography of advertising in postmillennial South Korea, Flower of Capitalism: South Korean Advertising at a Crossroads details contests over advertising freedoms and obligations among divergent vested interests while positing far-reaching questions about the social contract that governs advertising in late-capitalist societies. The term "flower of capitalism" is a clichéd metaphor for advertising in South Korea, bringing resolutely positive connotations, which downplay the commercial purposes of advertising and give prominence to its potential for public service. Historically, South Korean advertising was tasked to promote virtue with its messages, while allocation of advertising expenditures among the mass media was monitored and regulated to curb advertisers' influence in the name of public interest. Though this ideal was often sacrificed to situational considerations, South Korean advertising had been remarkably accountable to public scrutiny and popular demands. This beneficent role of advertising, however, came under attack as a neoliberal hegemony consolidated in South Korea in the twenty-first century. Flower of Capitalism examines the clash of advertising's old obligations and new freedoms, as it was navigated by advertising practitioners, censors, audiences, and activists. It weaves together a rich multi-sited ethnography--at an advertising agency and at an advertising censorship board--with an in-depth exploration of advertising-related controversies--from provocative advertising campaigns to advertising boycotts. Advertising emerges as a contested social institution whose connections to business, mass media, and government are continuously tested and revised. Olga Fedorenko challenges the mainstream notions of advertising, which universalize the ways it developed in Transatlantic countries, and offers a glimpse of what advertising could look like if its public effects were taken as seriously as its marketing goals. A critical and innovative intervention into the studies of advertising, Flower of Capitalism breaks new ground in current debates on the intersection of media, culture, and politics.